Legionella antimicrobial sensitivity testing: comparison of microbroth dilution with BCYE and LASARUS solid media. (26th December 2020) - Portal, Edward; Sands, Kirsty; Portnojs, Artjoms; Chalker, Victoria J; Spiller, Owen B
Abstract: Objectives: There is a lack of international unification for AST methodology for Legionella pneumophila . Current literature contains multiple possible methods and this study compares each of them to determine methodological concordance. Methods: Antibiotic susceptibility of 50 L. pneumophila strains was determined using broth microdilution (BMD), serial antimicrobial dilution in traditional buffered charcoal yeast extract (BCYE) agar (as well as comparison with gradient strip overlay on BCYE) and in a novel charcoal-free agar (LASARUS) for rifampicin, azithromycin, levofloxacin and doxycycline. Results: The deviation of tested media relative to BMD highlighted the overall similarity of BMD and LASARUS across all antimicrobials tested (within one serial dilution). BCYE agar dilution showed an increased MIC of up to five serial dilutions relative to BMD, while MICs by gradient strip overlay on BCYE were elevated by two to three serial dilutions, with the exception of doxycycline, which was decreased by three serial dilutions relative to MIC values determined by BMD. The MIC range for azithromycin was wider than for other antimicrobials tested and found to be caused by the presence or absence of the lpeAB gene. Conclusions: BMD-based antimicrobial susceptibility testing (AST) methodology should be the internationally agreed gold standard for Legionella spp. AST, as is common for other bacterial species. Traditional BCYE gave significantly elevated MIC results and its use should be discontinued for Legionella spp., while MIC determination using LASARUS solid medium gave results concordant (within one serial dilution) with BMD for all antimicrobials tested. To the best of our knowledge, this study is the first to identify the lpeAB gene in UK isolates.